2014
DOI: 10.1186/s40623-014-0153-3
|View full text |Cite
|
Sign up to set email alerts
|

Friction properties of the plate boundary megathrust beneath the frontal wedge near the Japan Trench: an inference from topographic variation

Abstract: The 2011 Tohoku-Oki earthquake (Mw 9.0) produced a fault rupture that extended to the toe of the Japan Trench. The deformation and frictional properties beneath the forearc are keys that can help to elucidate this unusual event.In the present study, to investigate the frictional properties of the shallow part of the plate boundary, we applied the critically tapered Coulomb wedge theory to the Japan Trench and obtained the effective coefficient of basal friction μ ′ b À Áand Hubbert-Rubey pore fluid pressure ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 35 publications
1
31
2
Order By: Relevance
“…in which a patch of the shallow fault zone accumulates significant elastic strain energy [Kato and Yoshida, 2011;Kennett et al, 2011;Matsubara and Obara, 2011;Koge et al, 2014] are inconsistent with the observed damage zone properties at the JFAST site, a location of inferred coseismic slip. If our interpretations are correct, great earthquakes like the 2011 M w 9.0 Tohoku-oki event could rupture to the trench without a shallow strong fault patch.…”
Section: 1002/2015jb012311mentioning
confidence: 68%
“…in which a patch of the shallow fault zone accumulates significant elastic strain energy [Kato and Yoshida, 2011;Kennett et al, 2011;Matsubara and Obara, 2011;Koge et al, 2014] are inconsistent with the observed damage zone properties at the JFAST site, a location of inferred coseismic slip. If our interpretations are correct, great earthquakes like the 2011 M w 9.0 Tohoku-oki event could rupture to the trench without a shallow strong fault patch.…”
Section: 1002/2015jb012311mentioning
confidence: 68%
“…Observational evidence of failure mode reversal in the frontal wedge during a single megathrust event is still incomplete. Koge et al (2014) found that a portion of the wedge above the large slip area of the 2011 Tohoku earthquake with a high taper angle (indicating high basal friction) hosted normal fault activity during or after the Tohoku mainshock (indicating low basal friction, also see Cubas et al, 2013). They explained this seemingly contradictory observation by a switch of the stress state in the wedge from compressionally critical to extensionally critical, due to a basal friction evolution from statically strong to dynamically weak.…”
Section: Model Application To Dynamic Rupture and Observational Resultsmentioning
confidence: 96%
“…The rupture evolution from full-crack-like to half-crack-like (Fig. 8) leads to early compressional failure overprinted by later extensional failure during a single megathrust event, which might be the case for the frontal wedge during the 2011 Tohoku earthquake (Koge et al, 2014). A similar scenario may have also occurred in the Nankai Trough, based on a similar current stress state in the frontal wedge between the Nankai Trough and the Japan Trench (Lin et al, 2015).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…(1)The Nankai trough (14 papers; Sugihara et al 2014, Tsuji et al 2014, Idehara et al 2014, Akuhara and Mochizuki 2014, Hyodo et al 2014, Takahashi et al 2014, Yamada and Shibanuma 2015, Takeshita et al 2014, Hino et al 2015, and Toki et al 2014) (2)The Japan trench (6 papers; Aochi and Ide 2014, Koge et al 2014, Sawai et al 2014, and Boston et al 2014) (3)Other trenches and fault zones (4 papers; Maekawa et al 2014, Namiki et al 2014) and ancient accretionary complexes and faults on land (7 papers; Schumann et al 2014, Hamahashi et al 2015, Kogure et al 2014, and Hashimoto and Yamano 2014) (4)Theoretical treatments of fracture and earthquake (2 papers; Kame et al 2014 andNishiyama et al 2014) The papers are also categorized into three scientific issues, focusing on different regions within each topic:…”
mentioning
confidence: 99%